Short- and long-term survival of children treated with ventricular assist devices in Spain, based on 15 years' experience. (9th February 2023) - Menéndez, Juan José; Sánchez-Galindo, Amelia Caridad; Balcells, Joan; Tejero-Hernández, María Ángeles; Ferrer-Barba, Ángela; Ibiza-Palacios, Emilio; Medrano-López, Constancio; Gran, Ferran; Frías-Pérez, Manuel Ángel; García-Vieites, María; Cano-Sánchez, Ana; Polo, Luz; et al.
Abstract: OBJECTIVES: To describe the use of ventricular assist devices (VAD) in children in Spain and to identify variables related to survival. METHODS: This is an observational cohort study of all children younger than 18 years of age who underwent an initial implantation of a VAD at any of the 6 paediatric heart transplant centres from May 2006 to December 2020. Subjects were identified retrospectively from each hospital's database. RESULTS: Paracorporeal VADs were implanted in 118 children [pulsatile (63%), continuous (30.5%) or both types (5.9%)]. Small children (<0.7 m 2 of body surface area) comprised the majority of this cohort (63.3%). Overall, 67% survived to VAD explantation, and 64.9% survived to hospital discharge. Non-central nervous system haemorrhage (39%) and stroke (38.1%) were the most common complications. Body weight <5 kg, congenital heart disease, pre-implantation bilirubin >34 μmol/l and bridge to decision strategy were associated with a higher mortality at hospital discharge and in the long-term. Interagency registry for mechanically assisted circulatory support (INTERMACS) status 1 and cardiac arrest prior to VAD implantation were related to long-term mortality, whereas pre-implantation renal replacement therapy and extracorporeal membrane oxygenation were not related to mortality. CONCLUSIONS: In Spain, 67% of the VAD-supported children have been bridged to heart transplantation or to recovery. Body weight lower than 5 kg, congenital heart disease diagnosis, cholestatic liver dysfunction, bridge to decision as VAD strategy, INTERMACS-1 status and cardiac arrest were pre-implantation variables related to mortality, whereas pre-implantation renal replacement therapy and extracorporeal membrane oxygenation were not. Abstract : Ventricular assist devices (VADs) have become the mainstay of management of end-stage heart failure in children waiting for heart transplant and their use has yielded a significant reduction in the waiting list mortality [1].